
Why is this zero?
I am reading my text, and they make a jump that I don't understand, and they don't give any explanation for it.
Sorry, I couldn't figure out how to put this stuff in latex...
mu=mean....greek letter (in particular, not m*u)
It gives the sum from i=1 to n of (xix bar)^2 + 2*(x barmu)*sum from i=1 to n of (xix bar)+n(x barmu)^2
It then says that this is equal to
sum from i=1 to n of (xix bar)^2 + n(x barmu)^2
Essentially they seem to be saying that
2*(x bar mu)*sum from i=1 to n of (xix bar)
is zero
Is it because x bar mu is 0? I didn't think this was the case......why is this middle term zero?

The sum is zero, NOT *(x bar mu)*
Because